Heat Production by the Denitrifying Bacterium Pseudomonas fluorescens and the Dissimilatory Ammonium-Producing Bacterium Pseudomonas putrefaciens during Anaerobic Growth with Nitrate as the Electron Acceptor - Samuelsson, M.-O. (1988)
The heat production rate and the simultaneous nitrate consumption and production and consumption of nitrite and nitrous oxide were monitored during the anaerobic growth of two types of dissimilatory nitrate reducers. Pseudomonas fluorescens, a denitrifier, consumed nitrate and accumulated small amounts of nitrite or nitrous oxide. The heat production rate increased steadily during the course of nitrate consumption and decreased rapidly concomitant with the depletion of the electron acceptors. A mean experimental enthalpy change value of −800 kJ/mol of nitrate and a mean growth yield value of 33 g (dry weight)/mol of nitrate consumed were obtained for different concentrations of nitrate. For Pseudomonas putrefaciens, a dissimilatory ammonium producer, the nitrate consumption resulted in an accumulation of nitrite and nitrous oxide. Nitrite consumption commenced after depletion of the nitrate; consequently, two phases were noted in the heat production rate curve during growth. A mean experimental enthalpy change value of −810 kJ/mol of nitrate was obtained for different concentrations of nitrate.